2018
DOI: 10.4236/ajps.2018.93032
|View full text |Cite
|
Sign up to set email alerts
|

Yield Response of Direct Seeded <i>Aus</i> Rice Varieties under Rainfed Condition

Abstract: Rainfed Aus rice is a popular conventional rice cultivation technique that through appropriate variety selection can accelerate the benefits of the farmer. On this context, an experiment was carried out at the research field of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur1706 from April to August in 2014 to evaluate yield performance of some Aus rice varieties under rainfed condition. The experiment was laid out in a split plot design with three replications. The experiment consisted of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Mymensingh recorded the lowest maturity period (146 days) and the highest (153 days). Ghosh et al (2015) supports the idea that genotypic variations may contribute to differences in maturity.…”
Section: Days To Maturitysupporting
confidence: 75%
“…Mymensingh recorded the lowest maturity period (146 days) and the highest (153 days). Ghosh et al (2015) supports the idea that genotypic variations may contribute to differences in maturity.…”
Section: Days To Maturitysupporting
confidence: 75%
“…Lowest maturity period was recorded in Mymensingh (147 days) and Highest at Jamalpur (152 days). Maturity might differ due to genotypic differences which is supported by Ghosh et al [9], who has recorded variation of days to maturity due to different varieties and Haque et al [10] reported wide genotypic variation in phenological events among 14 Aus cultivars. The duration also may depend on cultural management, soil and climatic conditions (edaphic factors) which agrees with Ahmed et al [11].…”
Section: Days To Maturitymentioning
confidence: 86%